Computer Generated Holograms Applied to 2D and 3D Objects - Labora, Marites; Bulanon, Harold; Manlosa, Armilyn; Lawas, Georgia; Sicam, Victor Arni (Science Diliman: A Journal of Pure and Applied Sciences; Vol 13 No 2 (2001), 2012)
The production of holograms using conventional techniques is a tedious job which is sensitive to many influences (Bulanon, 1999). During the recording process high stability of the experimental set-up is required to achieve a satisfying result. The production of holograms using the computer is a recently developed technique which provides an alternative for this demanding procedure (Trester, 1996; Fetthauer, 1995; Kato & Sakuda, 1992). In computer generated holograms (CGH) the interference pattern between the object wave and reference wave is calculated directly. By using standard equipment available in every office, like printers and copiers we can avoid the use of more difficult photographing techniques (Walker, 1999). We started to apply this technique to construct holograms of 2D objects. Presently, the procedure is being modified to apply this technique to 3D objects, a method which incorporates stereographic technique.